The association of anthropometric indices and cardiac function in healthy adults - Shahabi, Javad (ARYA Atheroscler, 2019)
BACKGROUND: Obesity is a major risk factor for many diseases including cardiovascular diseases (CVDs). Recently, it has been shown that upper body obesity can predict CVDs per se. In this study, we aimed to determine the association between indicators of upper body obesity and echocardiographic indices. METHODS: In this cross-sectional study conducted in Hajar Hospital in Shahrekord, Iran, from March to August 2014, 80 healthy adults were included. Participants’ neck circumference (NC), waist circumference (WC), body mass index (BMI), and blood pressure were measured. Echocardiography was performed for all participants, and echocardiographic indices such as early (E’) and late (A') diastolic tissue velocity, early (E) and late (A) transmitral flow velocity, E/E’ ratio, pulmonary arterial pressure (PAP), and left atrial volume (LAV) were recorded. The association between these indices were investigated using bivariate Pearson correlation coefficient. RESULTS: For men, NC had a significant correlation with LAV, systolic blood pressure (SBP), diastolic blood pressure (DBP), PAP, and A', and a negative correlation with E′. WC had a significant correlation with LAV, SBP, and PAP, and a negative correlation with E′, while BMI had a significant correlation with LAV, PAP, SBP, A, and A’. For women, NC had a significant positive correlation with LAV, A, ejection fraction (EF), SBP, PAP, and A’, and a negative correlation with E′ and E/E′. WC had a significant positive correlation with LAV, DBP, PAP, A, A’, and a negative correlation with E′, while BMI had a significant correlation with LAV, EF, SBP, PAP, E’, A, and A’. CONCLUSION: The positive correlation of NC with SBP, A, and A', as well as NC, WC, and BMI with LAV and PAP in both sexes, and the negative correlation of NC with E′ show the importance of these measures in estimation of metabolic and cardiovascular risk factors.